The Effect of Product Innovation, Value Co-Creation on Marketing Performance of a SMEs in Covid-19 Pandemic Era - Rahmawati, Fauziyah; Novani, Santi (Master of Management Diponegoro University, 2021)
This study aims to analyze product innovation and value co-creation on marketing performance in this pandemic covid-19. SMEs of food and beverage used as a sample. Sampling was done using a purposive sampling technique. Data were collected using a self-administered questionnaire. This study uses 34 data from MSMEs in the food and beverage sector affected by COVID-19. Partial Least Square (PLS) on Structural Equation Modeling (SEM) was chosen as the research method in this study. The results show that value co-creation have a significant effect on marketing performance. Product innovation negatively and not significant effects on marketing performance, and value co-creation significantly affect product innovation. The novelty in this study is a phenomenon that occurs; that is when the Covid-19 pandemic spreads in Indonesia. This study's limitation is needed to add other variables beyond the variables already in the model. This study only focused on SMEs for the food and beverage sector